2022
DOI: 10.1177/15248380221126183
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Intimate Partner Violence Victimization: A Systematic Review

Abstract: Person-centered approaches, such as latent class analysis (LCA) and latent profile analysis (LPA), aid the identification of subgroups within sample populations. These methods can identify the patterns of co-occurrence between different forms of intimate partner violence (IPV), providing valuable information for prevention and intervention efforts. The aim of this systematic review was to yield a summary and conduct a critical evaluation of the current research that utilizes LCA/LPA to investigate IPV victimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
5
3
2
Order By: Relevance
“…However, the latter finding seems to be inconsistent with previous research (Hall et al, 2022;Lagdon et al, 2023). One possible explanation could be cultural norms.…”
Section: Comparing Classes In Terms Of Psychological Correlates Of Ipvcontrasting
confidence: 93%
See 4 more Smart Citations
“…However, the latter finding seems to be inconsistent with previous research (Hall et al, 2022;Lagdon et al, 2023). One possible explanation could be cultural norms.…”
Section: Comparing Classes In Terms Of Psychological Correlates Of Ipvcontrasting
confidence: 93%
“…In parallel with our results, studies have shown that women who experienced severe and multiple forms of violence from their partners reported negative mental health outcomes (Ansara & Hindin, 2010;Armour & Sleath, 2014;Sipsma et al, 2015;Young-Wolff et al, 2013). However, while the vast majority of the prior studies have examined depression as a poor mental health sign (Clark et al, 2019;Hall et al, 2022;Weiss et al, 2017), our findings suggest the associated mental health outcomes may be broader. In other words, we contribute to the results suggesting that when survivor women experience multiple forms of IPV, it may increase their vulnerability to developing severe depression, anxiety, and somatization.…”
Section: Comparing Classes In Terms Of Psychological Correlates Of Ipvsupporting
confidence: 87%
See 3 more Smart Citations